The molecular components of phospho and glycolipid metabolism in plant cell membranes under the phosphorus deficiency - Svietlova, N.B. (Вiopolymers and Cell, 2012)
One of the aspects of molecular regulation of phosphorus metabolism in plants, the lipid components of membrane structures, has been reviewed. The refocusing of phosphoand glycolipid metabolism is an indicator of phosphorus accessibility in plants. The compensatory mechanisms of substitution of phospholipids with non-phosphorus containing glycolipids in membranes, allow plants to adapt to the phosphate (Pi) starvation. Phospholipids are the reserve pool of cellular phosphorus at reutilization of ions in the donor-acceptor system of plants. The mechanisms of transcriptional regulation of genes involved in the synthesis of phospholipids and glycolipids under Pi deficit have been analyzed. Обзор посвящен одной из составляющих молекулярной регуляции метаболизма фосфора в растительном организме – липидным компонентам мембранных структур. Изменение направленности метаболизма фосфои гликолипидов является показателем доступности фосфора растениям. Компенсаторные механизмы замещения фосфолипидов нефосфоросодержащими гликолипидами в мембранах позволяют растениям адаптироваться к условиям ограничения поступления фосфатов (Pi), а фосфолипиды служат резервным пулом клеточного фосфора при реутилизации ионов в донорно-акцепторной системе. Проанализированы механизмы транскрипционной регуляции генов, причастных к синтезу фосфои гликолипидов в условиях дефицита Pi. Огляд присвячено одній із складових молекулярної регуляції метаболізму фосфору в рослинному організмі – ліпідним компонентам мембранних структур. Зміна спрямованості метаболізму фосфоі гліколіпідів є показником доступності фосфору рослинам. Компенсаторні механізми заміщення фосфоліпідів нефосфоровмісними гліколіпідами у мембранах дозволяють рослинам адаптуватися до умов обмеження надходження фосфатів (Рі), а фосфоліпіди слугують резервним пулом клітинного фосфору за реутилізації іонів у донорно-акцепторній системі. Проаналізовано механізми транскрипційної регуляції генів, залучених до синтезу фосфоі гліколіпідів за умов дефіциту Pi.